Differences in anthropometric variables and muscle strength in relation to competitive level in male handball players - Lijewski, M.; Burdukiewicz, A.; Stachon, A.; Pietraszewska, J. (PLOS ONE, 2021)
Somatic characteristics manifested in different body morphology have great importance for the selection of athletes in most sports. The aim of our study is to evaluate the differences in anthropometric variables and isometric strength of handball players presenting different levels of sports competence, and to study the discriminative power of selected morphological characteristics that do not change in the training process. The study included the results of anthropometric measurements routinely used to monitor athletes, and body proportion indices were calculated. Fat percentage was assessed using the BIA, whereas body build was assessed using the Heath-Carter method. Measurements of right and left hand grip strength and back strength were taken. The results of measurements and calculations were analyzed using statistical methods. It was shown that players presenting the highest level dominate by the overall size and massiveness of the body, characteristics ensuring an advantage in direct confrontation. The size of subcutaneous fat tissue and percentage of body fat varied poorly between athletes in each group. Muscle strength assessed under static conditions shows a gradient in magnitude across teams from higher to lower rank, but the differences are not statistically significant. The same somatotype (balanced mesomorph) was present in all groups. Athletes presenting high sports level are characterized by body proportions that determine biomechanical conditions conducive to optimizing the structure of movements important in handball. Stepwise discriminant analysis showed that throwing-related characteristics (hand length, upper arm length, upper limb span, lower limb length) account for 88% of the variance in team ranking and can be used to identify the morphological predisposition of adepts to play handball.